Dynamical susceptibilities of the Falicov-Kimball model with correlated hopping: general approach - Shvaika, A.M.; Farenyuk, O.Ya. (Condensed Matter Physics, 2009)
The Falicov-Kimball model with correlated hopping is studied in the limit of in nite spatial dimensions. Dynamical susceptibilities are calculated using the generalization of the Dynamical Mean-Field Theory (DMFT), which is based on expansion over electron hopping around the single-site limit. A special case of semi-elliptic density of states and diagonal correlated hopping is considered numerically and the absence of phase transition for all temperatures except T = 0 is demonstrated, which corresponds to the known results.